«ГАЛОГЕНЛАР» МАВЗУСИНИ ЎҚИТИШДА ПЕГАГОГИК ВА ИНФОРМАЦИОН ТЕХНОЛОГИЯЛАРДАН ФОЙДАЛАНИШ - Ажиева, М.Б.; Ажиева, Б.А. (SCIENCE and SOCIETY, 2021)
This article describes the use of new didactic materials for teaching topic halogen.
Keywords: halogen; didactics; chemistry; fluorine; chlorine